Menuju Pantai Lasiana yang Luar Biasa: Optimalisasi Fasilitas, Aksesibilitas, dan daya tarik untuk Meningkatkan Kepuasan Wisatawan - fernando saragih; Andri Paulus Loe; Jibrael Mau (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
Tourism is one of the factors that can drive the economic growth of a country. Outstanding tourism enhances tourist satisfaction and positively impacts various related sectors. The development of tourism is closely related to facilities, accessibility, and tourist attractions. Based on this background, this study focuses on tourist satisfaction and the various factors influencing it. The aim of this research is to analyze how facilities, accessibility, and tourist attractions affect tourist satisfaction at a destination with tremendous potential. This study was conducted at Lasiana Beach with a sample size of 108 tourists using an accidental sampling method. It employed a quantitative approach through a survey method, and data analysis was conducted using multiple linear regression with SPSS software. The results indicate that facilities and tourist attractions have a significant negative impact on tourist satisfaction, while accessibility has a significant positive impact on tourist satisfaction.